Pengaruh Pemberian Ekstrak Daun Kelor (Moringa oleifera) terhadap Kadar Kolesterol pada Akseptor KB Suntik 3 Bulan di Kelurahan Mojoroto Kecamatan Mojoroto Kota Kediri - Husna, Nilna Hidayatul; Kundarti, Finta Isti; Wijayanti, Lumastari Ajeng; Titisari, Ira (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2023)
Family planning acceptance in Indonesia is high and injectable contraceptives have the highest prevalence. Long-term use of hormonal contraceptives causes changes in lipid metabolism. Moringa has the activity of lowering cholesterol levels. The purpose of this study was to determine the effect of moringa leaf extract (Moringa oleifera) on cholesterol levels. This research method uses a quasy experiment with a sample of 66 respondents consisting of 33 intervention group respondents who were given moringa leaf extract for 28 days and 33 control group respondents) with simple random sampling technique. Data analysis using t test. The results of the paired t test on cholesterol levels in the intervention group showed significant results, namely p value 0.000. The paired t test results on cholesterol levels in the control group showed insignificant results, namely p value 0.532. The results of the independent sample test on cholesterol levels in both groups showed a significant p value of 0.000. Cholesterol levels decreased after giving moringa leaf extract to 3-month injectable birth control acceptors. Health workers can motivate people to utilize moringa plants as a treatment in lowering cholesterol levels.